2017
DOI: 10.12681/eh.11597
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia-induced reproductive parasitism and applications

Abstract: Insects have been reported to be associated with a broad variety of microorganisms, affecting the host biology in many different ways. Among them, Wolbachia, an obligatory intracellular and maternally-inherited symbiont, has recently attracted a lot of attention. Beside insects, Wolbachia are found in association with a wide variety of other invertebrate species, including mites, scorpions, spiders, crustaceans, filarial nematodes. Several surveys have indicated that Wolbachia may be symbiont of up to 70% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 96 publications
0
6
0
1
Order By: Relevance
“…Drosophila simulans infected with Wolbachia are less effective in resisting eggs laid by the parasitoid Leptopilina heterotoma Thomson. Similarly, Wolbachia infection of L. heterotoma makes the parasitoid more vulnerable to the host's defenses (Fytrou et al., ; Saridaki & Bourtzis, ). Tagami et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila simulans infected with Wolbachia are less effective in resisting eggs laid by the parasitoid Leptopilina heterotoma Thomson. Similarly, Wolbachia infection of L. heterotoma makes the parasitoid more vulnerable to the host's defenses (Fytrou et al., ; Saridaki & Bourtzis, ). Tagami et al.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila simulans infected with Wolbachia are less effective in resisting eggs laid by the parasitoid Leptopilina heterotoma Thomson. Similarly, Wolbachia infection of L. heterotoma makes the parasitoid more vulnerable to the host's defenses (Fytrou et al, 2006;Saridaki & Bourtzis, 2009). Tagami et al (2001) reported that the embryonic mortality of Wolbachiainfected strains of Trichogramma evanescens Westwood and T. cacoeciae was significantly higher than that of the non-infected lines.…”
Section: The Negative Effects Of Wolbachia Infectionmentioning
confidence: 99%
“…This abundant group of obligate intracellular bacteria is widespread among arthropods, and its multiple strains frequently affect the reproductive biology of their hosts in diverse ways (Biondi, Guedes, Wan, & Desneux, 2018;Correa & Ballard, 2016;Engelstädter & Telschow, 2009). As a consequence, Wolbachia exhibits potential for use in arthropod pest management, either in sterile insect techniques (or incompatible insect techniques) and/or in the introduction of fitness-reducing factors in pest populations (Bourtzis, 2008;Saridaki & Bourtzis, 2009;Werren, Baldo, & Clark, 2008). However, while compromising the insect reproductive biology this endosymbiont may impair important management tools when determining parthenogenesis and/or other sexual aberrations such as sex-specific lethality and conversion of sexuality.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism is not well known, Wolbachia-induced CI has received considerable attention as a mechanism to control insect vectors and diseases. Wolbachia is responsible for inducing a number of reproductive modifications that enables its spread and maintenance in natural populations (Saridaki and Bourtzis, 2009;Guruprasad et al, 2013).…”
Section: Invasion Of Mosquito Populations and Host Biologymentioning
confidence: 99%